Aplicação da técnica de pesquisa do linfonodo sentinela no estadiamento do carcinoma gástrico - Fernando Augusto de Vasconcellos Santos (2009)
Gastric adenocarcinoma patients has lymph node metastases as an independently prognosis factor. Radical limphadenectomy can improve survival but also can increase surgical morbidity. As a principle, sentinel node navigation surgery (SNNS) could avoid unnecessary lymphadenectomy without compromising the prognosis. In this study 24 patients with gastric adenocarcinoma were initially screened to SNNS. Among then twelve were excluded: seven because of advanced disease; one because of final diagnosis of peptic ulcer; two because they didn`t agree with their inclusion in the study and in two because it wasn`t possible to set up surgery with nuclear medicine personal. At twelve included patients, eight were female and the age was among 32 and 71 years old. Five patients had T2 tumors, five had T3 tumors and two, T1 tumors. In 33% of cases tumor had diameter greater than 5.0cm. Including all patients, 387 lymph nodes were excised with a median of 32.3 lymph node per patient. The SNNS was feasible in all patients, a minimum of one and maximum of ten sentinel node (SN) were found per patient, with a median of 4.5 SN. The detection success rate was 100%. The entire SN were located in N1 and N2 nodal level, 8.3% exclusively located in N1 level. In 70.9% of cases the SN were located at lymphatic group number 6 and 7. The SN sensibility for nodal staging was 91.6% with 8.3% of false negative. In four patients who were initially staged as N0, the SNs were submitted to multisection analyses and immunohistochemistry and their final staging persisted as N0 without micrometastases. In one negative case for nodal metastases based on SN analyses had metastases in lymph nodes other than SN, given an incidence of 20% for skip metastases. Among the 55 SN, 49 of them were identified by the association of patent blue with patent blue and technetium while 42 were identified by the association of technetium and technetium with patent blue. The SNNS is a reproducible procedure and the detection rate of SN in this study was of 100%. The micrometastases frequency was 0% and the skip metastase frequency was 20%. The tumor size, gastric tumor location and obesity were indepemdent factor that imposed some limitations over SN identification. The results of nodal multisection and immunohistochemistry didn`t change the initial nodal staging.